Well-known and Indeterminate Effects of Vitamin D - I. N. Zakharova; S. V. Yablochkova; Yu. A. Dmitrieva (Вопросы современной педиатрии, 2013)
The problem of vitamin D deficiency has a special importance nowadays, as, according to the data received in numerous studies, almost 1/2 of the world population suffer from hypovitaminosis D. Epidemiological data on provision of children of different age groups with cholecalciferol are shown in this article, as well as various modern approaches to assessment of vitamin D concentration in organism are determined. A special attention is devoted to conceptions of metabolism and biological functions of vitamin D, which consist not only in its positive influence on the osseous tissue condition, but also in numerous extraosseous effects.